DECONSTRUCTION OF THE METAPHYSICS OF PRESENCE IN PHENOMENOLOGY AND STRUCTURALISM - A. A. Polivoda (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
Purpose of the work is a description of critical position of J. Derrida on metaphysics of presence in phenomenological and structuralist discourses. As a philosophical strategy, deconstruction tries to destroy a violent hierarchy of terms, in which one term dominates the other according to its ontological or rational sense. Methodology of research is based on J. Derrida’s strategy of deconstruction, which tries to undermine the basic principles of knowledge and Western philosophy existence, for example, the opposition between nature and culture. In terms of J. Derrida, to deconstruct Western philosophy means to explore the tensions and contradictions in text, which should clarify false reliability of accepted hierarchies. The originality of the work lies in the identification of metaphysic of presence problem in structuralist and phenomenological discourses through the deconstruction project. Deconstruction should show instability of logocentrism, which focuses on repression of writing in terms of thought, truth, reason or logic. Conclusions: J. Derrida’s deconstruction appeared as an attempt to overthrow metaphysics and get focused on the concept of writing, which scope is limited by discourse. Deconstruction of metaphysics of presence is a continuous request of legitimacy of the existing logocentrism, and search of its weaknesses, aporias and contradictions, which make impossible the tradition, centered around mind.